Impact of macroeconomic policies in Trinidad and Tobago : the firm under adjustment - Harrison, Philomen (Palgrave Macmillan New YorkUS, 2002)
Examines the effects of structural adjustment policies on the development of the private sector. Focuses on firms in the private sector, specifically the manufacturing industry of Trinidad & Tobago over a period of years (1983-1994) within which fall the implementation of stabilization/adjustment policies of the IMF and World Bank.